1996
DOI: 10.1007/bf01457657
|View full text |Cite
|
Sign up to set email alerts
|

Localisation of VIP- and CGRP-like substances in the skin and sinus hair follicles of various mammalian species

Abstract: Using an ultrastructural postembedding immunogold technique, we demonstrated vasoactive intestinal polypeptide (VIP)- and calcitonin gene-related peptide (CGRP)-like immunoreactivity in the Merkel cell dense-cored granules of skin and sinus hair follicles of adult cat and dog. The VIP-like substance was located in cat Merkel cells while both VIP- and CGRP-like substances were colocalised in dog Merkel cells. In cat Merkel cells, the magnitude of labelling of VIP was qualitatively higher than in dog Merkel cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
0
14
0
1
Order By: Relevance
“…18 The function of noninnervated MCs is still unknown. Like innervated MCs, they synthesize numerous polypeptides and their receptors, which strongly suggests paracrine or autocrine communication, [128][129][130] such as regulatory functions associated with the metabolism of cutaneous cells. The skin contains an equivalent of the hypothalamus-pituitary-adrenal axis, leading to the suggestion that the cutaneous neuroendocrine system communicates through humoral and neural pathways to regulate the vascular, immune, or pigmentary systems.…”
Section: After Denervationmentioning
confidence: 99%
“…18 The function of noninnervated MCs is still unknown. Like innervated MCs, they synthesize numerous polypeptides and their receptors, which strongly suggests paracrine or autocrine communication, [128][129][130] such as regulatory functions associated with the metabolism of cutaneous cells. The skin contains an equivalent of the hypothalamus-pituitary-adrenal axis, leading to the suggestion that the cutaneous neuroendocrine system communicates through humoral and neural pathways to regulate the vascular, immune, or pigmentary systems.…”
Section: After Denervationmentioning
confidence: 99%
“…Moreover, we and others 153,154 have shown that SCF used as a cell growth promoter and a costimulator enhances the ability of mast cells to release TNF‐ α , an effect that has also been reported in relation to human mast cell mediators 155 . Other cytokines have been shown to be expressed by both canine and human mast cells 156–158 . Notably, Sinke et al 159 reported the production of IL‐4.…”
Section: Functional Characterization Of Canine Mast Cells: a Good Matmentioning
confidence: 99%
“…Some immunocytochemical studies have shown that these substances exist in MC granules (Weihe et al. , 1991; Cheng Chew & Leung, 1991, 1994, 1996; Hartschuh & Weihe, 1988). It is likely that these substances coexist with chromogranin A (Gauweiler et al.…”
Section: Introductionmentioning
confidence: 99%